D-Dimer Is a Diagnostic Biomarker of Abdominal Aortic Aneurysm in Patients With Peripheral Artery Disease - Cai, Huoying; Pan, Baihong; Xu, Jie; Liu, Shuai; Wang, Lei; Wu, Kemin; Yang, Pu; Huang, Jianhua; Wang, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background: Etiology and risk factors of peripheral artery disease (PAD) include age, smoking, and hypertension et al, which are shared by abdominal aortic aneurysm (AAA). Concomitance with AAA in PAD patients is not rare but easily overlooked in clinical situation though management strategies are altered totally. Aim of this study is to investigate diagnostic biomarkers for prediction of AAA in PAD patients. Methods: 684 patients diagnosed with AAA and/or PAD were enrolled and analyzed retrospectively. Each PAD and AAA patient was gender and age-matched. Demographic data, medical history, and serum laboratory tests profile were obtained. Statistical analysis was performed to determine diagnostic biomarkers of AAA in PAD patients. Results: Firstly, 320 PAD only patients and 320 AAA only patients were compared. Levels of bilirubin and D-dimer were decreased while incidence of diabetes mellitus, levels of fibrinogen and platelet count were increased significantly in PAD only patients compared with those in AAA only patients (P<0.001). Next, 364 PAD patients (44 AAA patients) and 364 AAA patients (44 PAD patients) were compared. Multivariate logistic regression analysis confirmed differential distribution of bilirubin, D-dimer, fibrinogen and platelet count between AAA patients and PAD patients (P <0.05). Receiver operator curves showed that area under curve (AUC) of total bilirubin, direct bilirubin, D-dimer, fibrinogen and platelet count was 0.6113, 0.5849, 0.7034, 0.6473, and 0.6785, respectively. Finally, to further validate predictive efficacy of mentioned markers, multivariable logistics regression analysis was performed between PAD only group and PAD with AAA group. Results suggested increased levels of D-dimer in PAD with AAA group compared to PAD only group (OR: 2.630, 95% CI:1.639-4.221; P<0 .001). Particularly, the Youden index suggested that cutoff value of D-dimer for predicting AAA in PAD patients was 0.675 mg/L with sensitivity of 76.9% and specificity of 84.9% (AUC=0.8673;95% CI, 0.8106-0.9240, P < 0.001). In all 364 PAD patients, 41.46% patients were diagnosed AAA when D-dimer > 0.675 mg/L while only 3.55% patients were diagnosed AAA when D-dimer ≤ 0.675 mg/L. Conclusions: PAD and AAA exert different clinical and serum profiles; D-dimer (> 0.675 mg/L) is a reliable biomarker for prediction of AAA in PAD patients.